Trade and real wages of the rich and poor: Evidence from Brazil and Mexico - Zheli He (Inter-American Development Bank (IDB), 2019)
Trade liberalization affects real-wage inequality through two channels: the distribution of nominal wages across workers and, if the rich and the poor consume different bundles of goods, the distribution of price indices across consumers. I provide a unified framework incorporating both channels by allowing for nonhomothetic preferences and worker heterogeneity across jobs. I parametrize the model for 40 regions using sector-level trade and production data and find that China's productivity growth decreases the relative nominal wage of the poor and the relative price index for the poor in Mexico and Brazil. On net, real-wage inequality falls in the two countries in the baseline case.
Keywords: F14; F61; D31; 330; import competition; wage inequality